O que aprendo na escola é o que preciso para mudar a vida? Letramento na EAJA: encontro no desencontro - Carvalho, Wilma Martins (2005)
This research is the result of a studying that was realized next to students from Teenagers, Youngs and Adults Education - EAJA, from 1st to 4th series of a school from Municipal Department of Education - SME from Goiânia. We have shown a historical approach of young and adults s breeding, as well as the propose of Teenagers, Youngs and Adults - EAJA. Through decades, professionals in education have been sought methods and practices in keeping with the cultural reality of the Youngs and Adults upbringing. Studious of education perceive the efforts from educationalists and theorists to obtain the dimension of the complexity of this modality of Teaching, and that it has a long way to examine. The aim is to break up with concerning banks practices and to compose proposals that congive value to diversity in a which the fellows will be constructors Knowledge themselves. EAJA propose is to conduct school whose perspective does not hold with social exclusion, it enroll itself on the source of liberator upbringing and it has a deal to cooperate for a society more correct. In this way, we steer the focus investigation to the social practices about reading and writing that have been developed by students from EAJA in its social context, for we understand that these practices can contribute to the inclusion of the fellow in the lettered context. We have spoken, also about the theoric fundamentals that consist on the lettered, it was focalized by the optics cultural-historical approach. The qualitative research has guided the investigation by flexible observation and interview. The goal has gone to start from the facts historically built by the reciprocal informations and influences. According to this sense the fellow is discerned in his totality like human being in changing and modifying, and insert in a social-historical context that conect him with the inside and outside shapes. Considering the relation of fellows with reading and writing in the social context, we bring up a problem: do the EAJA students develop reading and writing social practices? This is what we propose ourselves to inquire.